3(7-y)-6*2=-21

Simple and best practice solution for 3(7-y)-6*2=-21 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(7-y)-6*2=-21 equation:


Simplifying
3(7 + -1y) + -6 * 2 = -21
(7 * 3 + -1y * 3) + -6 * 2 = -21
(21 + -3y) + -6 * 2 = -21

Multiply -6 * 2
21 + -3y + -12 = -21

Reorder the terms:
21 + -12 + -3y = -21

Combine like terms: 21 + -12 = 9
9 + -3y = -21

Solving
9 + -3y = -21

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + -9 + -3y = -21 + -9

Combine like terms: 9 + -9 = 0
0 + -3y = -21 + -9
-3y = -21 + -9

Combine like terms: -21 + -9 = -30
-3y = -30

Divide each side by '-3'.
y = 10

Simplifying
y = 10

See similar equations:

| 2.3g=7013 | | 5x+6a+7= | | 2x+.25x=54 | | 12w-8=28 | | 2x+13.6=0.4x | | 23a=30 | | 3x-7x+4= | | 8k+7k=0 | | 4(w+7)-(-3w-9)=6w | | 7.5x-1.5x=6.6 | | 29x^2-12x=0 | | m^2-24m=-144 | | 3x^2-7x+12=0 | | 4(4y+2)=(1+6y)+8 | | 4(z-5)+2=x+3 | | 11x-14y=13 | | -5z-9=-24 | | 3x+9=9x-21 | | 25x^3-20x^2+20x-16= | | 156=50+w | | x+16=2(4x+8) | | Y-0.6=2(x-0.8) | | 0=x^2-29x-108 | | x+8=2(2x+7) | | 4+3d=262 | | 8(x+5)=7(x-7) | | x+8=4x+21 | | 2(4x-9)-6x=0 | | X*X-15X=0 | | 2-2w=26 | | x+8=4x+22 | | 3x-2=4x+10 |

Equations solver categories